Juveniles versus adults: differences in PGE2 levels in the gingival crevicular fluid during orthodontic tooth movement - Chibebe,Priscilla Campanatti (2010)
This study aimed to investigate age-related changes in the biosynthetic capacity of prostaglandin E2 (PGE2) in the gingival crevicular fluid (GCF) during one month of orthodontic treatment. Twenty-five juvenile subjects (mean age 13 ± 2.1 years) and 23 adults (mean age 24 ± 2.1 years) were included. GCF was collected immediately before the force application at the baseline, 2, 21 and 28 days, with periopaper inserted into the gingival crevice of the maxillary lateral incisors. The mediator levels were determined with an EIA kit. The results showed that the PGE2 concentrations were significantly elevated from the baseline to 21 days (129.35 and 198.84 pg/µL, p = 0.0169) in juvenile subjects and reduced from 21 to 28 days (198.84 to 112.60 pg/µL, p = 0.0032). Adults, however, had no significant changes in the PGE2 levels. The total amounts of PGE2 from both groups changed between the baseline to 21 and 21 to 28 days (p = 0.0119 and p = 0.0076, respectively). The PGE2 initial and final levels showed significant differences between the juveniles and adults, being higher in adults (baseline: juvenile = 129.35 pg/µL vs. adult = 163.20 pg/µL, p = 0.0379; t3: juvenile = 112.60 pg/µL and adult = 175.30 pg/µL, p = 0.0005). In conclusion, the results demonstrate the presence of variation in the PGE2 levels according to age and the orthodontic activation period, which can explain why the speed of orthodontics treatment may be different in adults vs. juveniles.